Peculiarities of a Land Plot Legal Status as an Item of Immovable Property - Vladimirovna Efimova, Olga; Sergeevna SmaginÐ°, Olga; Romanovna Lenkovskaya, Renata; Andreevna Neznamova, Alla; Aleksandrovna Volkova, Maria (International Journal of Engineering and Technology, 2018)
The article reviews attributes of immovable things, a land plot in particular, as a special form of an immovable thing. The authors have analyzed conceptual documents and legal precedents allowing identifying various items of immovable property and correlating them with each other. The article identifies gaps in the land legislation and civil legislation related to incomplete definitions and lack of clearly determined attributes of immovable things. The article reflects the latest changes in legislation characterizing a judicial attribute of any immovable property. Based on the identified attributes, in accordance with the Russian legislation, immovable property is divided into several groups. The authors identify a notion of a land plot as a special type of immovable property, without which the things may not exist and be divided into movable and immovable. Â